2015
DOI: 10.1007/s11250-015-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

A duplex PCR-based assay for simultaneous detection of Trypanosoma evansi and Theileria annulata infections in water buffaloes

Abstract: Trypanosomosis and bovine tropical theileriosis are important vector-borne protozoan diseases imposing some of the serious constraints on the health and productivity of domestic cattle in tropical and subtropical regions of the world. Following recovery from primary infection of both these conditions, animals become persistent carriers and act as reservoirs of infection thereby playing a critical role in disease epidemiology. The present study describes development and evaluation of duplex polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Several workers like Mahmood et al, (2010), Kolte et al, (2017), Paliwal et al, (2019), Kundave et al, (2015) have performed PCR using whole blood and also reported that PCR was most sensitive tool for diagnosis of theileriosis. Partial similar observations were recorded earlier by Ali and Radwan (2011), Ghanem et al, (2013), Chaisi et al, (2013, Sudan et al, (2015) and many other authors.…”
Section: Resultssupporting
confidence: 90%
“…Several workers like Mahmood et al, (2010), Kolte et al, (2017), Paliwal et al, (2019), Kundave et al, (2015) have performed PCR using whole blood and also reported that PCR was most sensitive tool for diagnosis of theileriosis. Partial similar observations were recorded earlier by Ali and Radwan (2011), Ghanem et al, (2013), Chaisi et al, (2013, Sudan et al, (2015) and many other authors.…”
Section: Resultssupporting
confidence: 90%
“…A total number of six animals were co-infected by both parasites 6 [3.5; 8.5] CI at 95% which was lower than cattle in India (11.25%) (Sudan et al 2015). The highest rate co-infection was observed in 2 to 5 years age group 8 [3; 13] CI at 95%.…”
Section: Resultsmentioning
confidence: 99%
“…The disease is caused by an apicomplexan parasite Theileria annulata and involves Hyalomma anatolicum anatolicum as its vector in the Indian subcontinent (Gill et al 1978). BTT is responsible for high rates of mortality in dairy cattle and about 200 million animals are supposed to be exposed to its risk (Radostits et al 1994;Sudan et al 2014Sudan et al , 2015. The global annual losses due to BTT are estimated to be of US$800 million (Brown 1997) while in India alone, the disease accounts for an approximate annual loss of US$384.3 million (Minjauw and McLeod 2003).…”
Section: Introductionmentioning
confidence: 99%